2022
DOI: 10.4274/jcrpe.galenos.2021.2020.0287
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Hypertrophy in Patients with X-Linked Hypophosphataemia

Abstract: X-linked hypophosphatemia (XLH) is a rare genetic disorder with X-linked dominant inheritance. Mutations in the PHEX gene increase fibroblast growth factor 23 (FGF23) concentrations, causing loss of phosphorus at the proximal tubule. Most pediatric patients debut in the first two years with short stature and bowed legs. Conventional treatment consists of oral supplements with phosphorus and calcitriol. Since 2018, burosumab has been approved as a novel therapeutic option for XLH, with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…There are no data of treatment of patients with other diseases with heart function abnormalities related to high FGF23 levels. 42 Previous studies have demonstrated that FGF23 levels are higher in obese individuals versus normal weight individuals and that BMI is positively correlated with FGF23 even in different study populations. 20,28,40,[43][44][45] In our study we found these results only in our control group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…There are no data of treatment of patients with other diseases with heart function abnormalities related to high FGF23 levels. 42 Previous studies have demonstrated that FGF23 levels are higher in obese individuals versus normal weight individuals and that BMI is positively correlated with FGF23 even in different study populations. 20,28,40,[43][44][45] In our study we found these results only in our control group.…”
Section: Discussionmentioning
confidence: 93%
“…There are no data of treatment of patients with other diseases with heart function abnormalities related to high FGF23 levels. 42 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond these merely observational studies, in a randomized trial of 120 CKD G3 patients, administration of the phosphate-binding drug sevelamer reduced FGF-23 levels significantly but had no impact on cardiac hypertrophy or function [40]. Furthermore, Takashi et al [41] did not observe the development of LVH in 24 adult patients with hypophosphatemic rickets, who are lifelong exposed to elevated plasma FGF-23, albeit these data were recently challenged [42].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Pediatric patients with XLH have increased prevalence of obesity ( 5 ) and evidence of unfavorable body composition ( 6 ), potentially placing them at risk for metabolic complications ( 7 ). Left ventricular hypertrophy (LVH) with several potential contributing factors has been reported in children affected by debilitating XLH ( 8 ). The chronic exposure to elevated levels of FGF23 have been proposed as a risk factor for cardiac morbidity, based upon its having been linked with cardiac hypertrophy in the context of chronic renal failure ( 9 ).…”
Section: Introductionmentioning
confidence: 99%